HUBUNGAN LAMA HEMODIALISIS DENGAN NAFSU MAKAN PADA PASIEN GAGAL GINJAL KRONIK DI UNIT HEMODIALISIS RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2019 - Arfah May Syara; Syatriawati Suhaimi; Anita Sri Gandaria Purba; Juni Mariati Simarmata; Cindy Yulvika Saragih (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
Hemodialysis patients are susceptible to malnutrition caused by components in hemodialysis, such as Dialyzer (Kidney Artificial), blood line, AV fistula, bicarbonate fluid, acidic liquid. Patients who have long been undergoing hemodialysis have high urea and creatinine levels. Increased levels of urea and creatinine can stimulate acid production such as stomach ulcers (gastritis), namely nausea, vomiting, heartburn, bloating and no appetite. This research aims to knowing long standing relationship of hemodialysis with appetite in patients chronic renal failure in the unit hemodialysis of Grandmed Lubuk Pakam Hospital in 2019. This type of research is quantitative research, using analytical survey method with cross sectional approach. The population in this study were all patients with chronic renal failure who were in the hemodialysis unit of Grandmed Lubuk Pakam Hospital with a sample of 49 people, using a purposive sampling technique. Data collection was using a questionnaire. The analysis in this study used Chi Square test with a degree of confidence of 5% = 0,05. The results of the study stated that the majority of respondents were in the old category (2 years-3 years) as many as 31 people (63.3%) with decreased appetite by 21 people (42.9%), fixed appetite of 7 people (14.3 %), appetite increased by 3 people (6.1%). There is a long standing relationship of hemodialysis with appetite in patients chronic renal failure in the unit hemodialysis of Grandmed Lubuk Pakam Hospital in 2019 with p value < Î± = 0,05.